Right at the Eye of the Storm: Human Resource Management Challenges Amid Covid - 19 Outbreak in Zimbabwe - Farai Ncube; Rumbidzai Tsandukwa; Pilot Ndhlovu (Africa Development and Resources Research Institute, 2023)
The corona virus pandemic has already been the major transform ati ve event to date in the entire history of human resource management. Within a space of 4 months the whole world of work has been grossly altered. The workplace and workforce impact of the pandemic, point out much more to adverse and troubling times for wor kers and organizations, placing HR right at the eye of the storm. Globally and more importantly locally all eyes are on HR practitioners as they help people navigate these unprecedented times and uncharted waters. I therefore attempt through the adopti on of secondary and primary data analyse the possible challenges impacting HR in the process , given that hard decisions around staffing levels, reducing workers’ hours and cutting costs wherever and however possible have to be made